Development of exposition text writing materials based on contextual approach - Sari, Arista M.; Rasyid, Yumna; Muliastuti, Liliana (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to develop teaching material for exposition text writing based on a contextual approach for class X high school students. This teaching material is needed to support students' ability to write exposition text. Based on the results of observation and analysis of initial needs, students find it difficult because the text used in the textbook used is not contextual so it is difficult to understand students. The research carried out was by using research and development method which refers to the development of Borg and Gall which is tailored to the needs. This study was designed according to the needs of students in class X BPS & K I Jakarta High School. The book cover is designed to describe the contents of the material in this product. The content of the product consists of seven materials. The material is (1) Composing the sentence of nominal and verbal sentences. (2) Introducing paragraph reasoning patterns. (3) Facts and opinions in the exposition text. (4) Arranging the first exposition text structure, namely the thesis. (5) Arranging the structure of the second epic text, namely classes. (6) Arranging the third exposition text structure that is the conclusion. (7) Arranging exposition texts with appropriate structures and rules. All material, examples, texts, exercises, and illustrations of images contained in the teaching materials are adapted to the environment in Jakarta. The presence of contextual teaching materials is expected to facilitate students to study exposition texts.